2008
DOI: 10.1016/j.jhealeco.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for drug rehabilitation: Implications for cost recovery

Abstract: Objectives-This study estimates the value that clients place on methadone maintenance and how this value varies with the effectiveness of treatment and availability of case management. We provide the first estimate of the price elasticity of the demand for drug treatment.Methods-We interviewed 241 heroin users who had been referred to, but had not yet entered, methadone maintenance treatment in Baltimore, Maryland. We asked each subject to state a preference among three hypothetical treatment programs that var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Among those who are currently prescribed OAT, receiving onsite psychological counseling at OAT sites appeared to be an important factor related to WTP. These findings are consistent with results elsewhere showing that clients would pay more for ancillary services like case management during their addiction treatment (Bishai et al 2008). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among those who are currently prescribed OAT, receiving onsite psychological counseling at OAT sites appeared to be an important factor related to WTP. These findings are consistent with results elsewhere showing that clients would pay more for ancillary services like case management during their addiction treatment (Bishai et al 2008). …”
Section: Discussionsupporting
confidence: 92%
“…Most prior studies used contingent valuation, indirect, technique to assess WTP for drug misuse treatment (Bishai et al 2008; Borisova & Goodman 2003; Tang et al 2007; Tran 2013; Zarkin et al 2000). Since our study was not originally designed to measure WTP for OAT, we used direct (reveled-preference) method to measure WTP and assessed factors associated with WTP for OAT among groups of PWID in Ukraine with different prior OAT experience.…”
Section: Introductionmentioning
confidence: 99%
“…Another proxy for treatment motivation and retention may be willingness to pay for treatment. In a study conducted among the participants in this trial, participants indicated they were willing to pay progressively more for treatment the longer they remained heroin-free (Bishai et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Depression, suicidality, and drug abuse states resulted in rehabilitative costs. [26][27][28] The U.S. cost of illness for HIV was extracted from Walensky et al 29 Cost of provider coverage was dependent on combinations of surgery and HRT. HRT was a fixed cost.…”
Section: Costsmentioning
confidence: 99%